GENERATION Z'S ETHICAL LEADERSHIP MODEL IN NATIONAL POLITICS: A STUDY OF CERINT IRALLOZA TASYA'S ROLE IN THE REGIONAL REPRESENTATIVE COUNCIL (DPD-RI) - Rizky Firnanda; Djorgie Prasandy; Wirza Khairunnisa; Novia Nirwana; Thomas Antoni (Jurnal Eduslamic, 2026)
Generation Z is increasingly demonstrating a strategic role in the national political sphere, not only as voters but also as leadership actors who carry ethical values ​​and character. This article examines the Ethical Leadership Model of Generation Z in the National Political Space through a study of Uni Cerint Iralloza Tasya, a young person from Minangkabau who is active in the Regional Representative Council of the Republic of Indonesia (DPD-RI). This research focuses on how character education shapes ethical leadership practices reflected in Uni Cerint's attitudes, values, and actions in carrying out her political role. The research approach used is qualitative with a character study method, through document analysis, interviews, and tracing activities and ideas displayed in the public sphere. The results show that the ethical leadership of Generation Z represented by Uni Cerint Iralloza Tasya is characterized by integrity, siding with the interests of the community, openness, and strengthening local Minangkabau values ​​that align with the principles of democracy and national political ethics. Character education, whether obtained through family, cultural environment, or formal education, plays a significant role in shaping moral awareness and social responsibility as a young leader. This article asserts that Generation Z's ethical leadership model has great potential to strengthen the quality of democracy and build value-oriented politics, particularly through the internalization of character education and local wisdom in national leadership practices.